Dual Diagnosis of Fragile X Syndrome and DEPDC5-Related Disorder Emphasizes DEPDC5’s Role Beyond Familial Epilepsy: A Case Report and Literature Review - Rory Edwards; Grace Murphy; Joshua W. Owens; Craig Erickson; Robert Hopkin; Amelle Shillington (Case Reports in Genetics)
Dep domain-containing Protein 5 (DEPDC5), encoded by the gene DEPDC5, regulates the cell cycle by inhibiting the mTORC1 pathway in response to amino acid deficiency. Loss of function DEPDC5 variants are recognized to present as focal familial epilepsy; however, associations with comorbid brain malformations and neurodevelopmental disorders have also been reported. mTOR inhibitors were found to benefit DEPDC5-knockout mice. Fragile X syndrome (FXS) is an X-linked neurodevelopmental disorder caused by loss of function of FMR1, and females are expected to have milder neurodevelopmental presentations than males. The reported individual is a 17-year-old female diagnosed with FXS at 1 year of age, but the severity of her neuropsychiatric symptoms prompted further genetic testing at age 14, revealing a likely pathogenic c.4307_4310del DEPDC5 variant. Following this diagnosis, she was started on the mTOR inhibitor sirolimus without significant clinical response. She has never been diagnosed with epilepsy; however, her DEPDC5 and FXS dual diagnosis was thought explanatory for her presentation. A review of 213 previously reported individuals with DEPDC5-related disorder demonstrated that 15.2% of individuals do not have epilepsy, 24.3% have intellectual disability, and 33.8% have brain malformations. Her lack of response to sirolimus may represent the presence of a critical treatment window for mTOR inhibitors in neurodevelopmental disorders.